Pengajaran Bahasa Arab untuk Tujuan-khusus: Satu Pandangan Awal [Teaching Arabic Language for special purposes: an early view] - Dahan, H.B.A.M.; Zailaini, M.A. (2005)
The issue of teaching languages for specific purposes is not new. It has been a topic of discussion years ago particularly in English teaching but not in Arabic teaching. This article looks into the possibility of exploring Arabic teaching for specific purposes at higher learning institutions with special reference to Academy of Islamic Studies, University of Malaya. Two skills, reading and writing, are discussed. The authors use the phrase “Satu Pandangan Awal” (A preliminary study) with hope that this topic will be discussed at length in future.